Motives for Saudi University Students to Use Smartphones and the Gratifications Achieved from Them: A survey study on a sample of Jazan University students (The International Journal of Educational Sciences and Arts, 2024)
This study aims to identify the motives for using smartphones by Saudi university students and to reveal the motives for using smartphones by Saudi university students and the satisfactions achieved from them, as well as to clarify the satisfactions achieved from students' use of smartphones and to identify the importance of using them. The researchers used the survey method, which is one of the well-known methods in the field of descriptive studies, using the questionnaire tool, which targeted a sample of Jazan University students, where the sample size reached 230 individuals. The study concluded that the cases in which the sample members use smartphones most are when connecting to the Wi-Fi network, and the circumstances of the sample members are what control the number of times they use the smartphone during the day, as there is no specific time for the sample members to use the smartphone. Also, obtaining information from the directive satisfactions achieved by the sample members from using the smartphone and opening topics with family and friends from the social satisfactions achieved by the sample members from using the smartphone.
Keywords: Uses and Gratifications; Motives; Smartphones; Saudi Universities